LEGAL PROTECTION FOR PARTIES WHEN MPD FAILS TO COLLECT NOTARIAL PROTOCOLS - Aurel, Adinda Mellinia; Herlindah, Herlindah; Sjafi'i, Imam Rahmat (Universitas Nurul Jadid, 2025)
The failure of the MPD to take the Notary protocol as stipulated in Article 63 paragraph (6) of the 2014 UUJN has legal consequences that could be detrimental to the parties. There are no further provisions regarding the mechanism for saving the protocol when the MPD does not take the Notary protocol, even though the Notary protocol is a collection of state archive documents that must always be stored and maintained. The UUJN only regulates the submission of the Notary protocol. The absence of complete regulations regarding the Notary protocol raises a legal issue, namely legal incompleteness. The method used is normative legal research. The results of the research are that the legal consequences of the MPD not taking the Notary protocol are 1. the loss of the rights of interested parties to obtain a grosse, copy, or excerpt of the deed. 2. the Notary protocol becomes neglected and is at risk of being damaged or lost. There are two types of legal protection provided to interested parties, namely preventive and repressive legal protection. Preventive legal protection refers to the MPD immediately taking the Notary protocol from the heirs who did not submit the protocol to the recipient so that the protocol remains stored and well maintained. Repressive legal protection refers to filing a complaint with the MPD so that the Notary protocol is immediately taken from the heirs and submitted to the Notary who received the protocol.